Diffuse Alveolar Hemorrhage After Pediatric Hematopoietic Stem Cell Transplantation - Fan, Kimberly; McArthur, Jennifer; Morrison, R. Ray; Ghafoor, Saad (Frontiers in Oncology, 2020)
Pulmonary complications are common following hematopoietic cell transplantation (HCT) and contribute significantly to its morbidity and mortality. Diffuse alveolar hemorrhage is a devastating non-infectious complication that occurs in up to 5% of patients post-HCT. Historically, it carries a high mortality burden of 60-100%. The etiology remains ill-defined but is thought to be due to lung injury from conditioning regimens, total body irradiation, occult infections, and other comorbidities such as graft versus host disease, thrombotic microangiopathy, and subsequent cytokine release and inflammation. Clinically, patients present with hypoxemia, dyspnea, and diffuse opacities consistent with an alveolar disease process on chest radiography. Diagnosis is most commonly confirmed with bronchoscopy findings of progressively bloodier bronchoalveolar lavage or the presence of hemosiderin-laden macrophages on microscopy. Treatment with glucocorticoids is common though dosing and duration of therapy remains variable. Other agents, such as aminocaproic acid, tranexamic acid, and activated recombinant factor VIIa have also been tried with mixed results. We present a review of diffuse alveolar hemorrhage with a focus on its pathogenesis and treatment options.